2-(Piperidin-4-yl)acetamides as Potent Inhibitors of Soluble Epoxide Hydrolase with Anti-Inflammatory Activity - Juan Martín-López; Sandra Codony; Clara Bartra; Christophe Morisseau; María Isabel Loza; Coral Sanfeliu; Bruce D. Hammock; José Brea; Santiago Vázquez (MDPI AG, 2021)
The pharmacological inhibition of soluble epoxide hydrolase (sEH) has been suggested as a potential therapy for the treatment of pain and inflammatory diseases through the stabilization of endogenous epoxyeicosatrienoic acids. Numerous potent sEH inhibitors (sEHI) have been developed, however many contain highly lipophilic substituents limiting their availability. Recently, a new series of benzohomoadamantane-based ureas endowed with potent inhibitory activity for the human and murine sEH was reported. However, their very low microsomal stability prevented further development. Herein, a new series of benzohomoadamantane-based amides were synthetized, fully characterized, and evaluated as sEHI. Most of these amides were endowed with excellent inhibitory potencies. A selected compound displayed anti-inflammatory effects with higher effectiveness than the reference sEHI, TPPU.